Bodyroll in front crawl swimming - Payton, C. J.; Sander, R. H. (World book of swimming: From science to performance, 2012)
The rolling actions of the shoulders and hips (bodyroll) in front-crawl and backstroke reflect the rhythmical contributions of the lower limbs, the actions of the upper limbs, and gravitational effects. The timing of the shoulder and hip rotations varies between and within swimmers, depending on speed, the stage of the race, and the nature of the kick (e.g. depth and frequency). A number of performance benefits have been attributed to bodyroll including reduced drag, increased stroke length, reduction in shoulder injury and increased propulsion.